LAKON PERTUNJUKAN WAYANG GOLEK PURWA DALAM KONTEKS FALSAFAH KEHIDUPAN MASYARAKAT SUNDA - Kusnendi, Cecep (Paraguna, 2018)
Wayang Golek   is  an  art that  has  lived for centuries.  As a cultural  product,  Wayang golek  is  full  of the   aesthetic-philosophical  values  of the   life  of the   Sundanese people.  These aesthetic-philosophical values are  infact explicitly contained in their stories,  both  from  the  Ramayana  epics,  as   well   as  from  the  Mahabarata  epics. These  educational   values  should  be   absorbed  easily   if the   conditions  of  the Sundanese people are quite  conducive  today.  The  Sundanese people are now  being swayed  by  the  proliferation  of "mass  culture",  causing the  essence  contained in traditional arts  ---  especially  Sundanese golek   ---almost  not  absorbed by  society. This  paper seeks  to  reintroduce  the   essence  of the   value   contained  in  wayang stories